Evaluation of Alpha-Ketoglutarate Supplementation on the Improvement of Intestinal Antioxidant Capacity and Immune Response in Songpu Mirror Carp (Cyprinus carpio) After Infection With Aeromonas hydrophila - Wu, Di; Fan, Ze; Li, Jinnan; Zhang, Yuanyuan; Wang, Chang’an; Xu, Qiyou; Wang, Liansheng (Frontiers in Immunology, 2021)
As an intermediate substance of the tricarboxylic acid cycle and a precursor substance of glutamic acid synthesis, the effect of alpha-ketoglutarate on growth and protein synthesis has been extensively studied. However, its prevention and treatment of pathogenic bacteria and its mechanism have not yet been noticed. To evaluate the effects of alpha-ketoglutarate on intestinal antioxidant capacity and immune response of Songpu mirror carp, a total of 360 fish with an average initial weight of 6.54 ± 0.08 g were fed diets containing alpha-ketoglutarate with 1% for 8 weeks. At the end of the feeding trial, the fish were challenged with Aeromonas hydrophila for 2 weeks. The results indicated that alpha-ketoglutarate supplementation significantly increased the survival rate of carp after infection with Aeromonas hydrophila (P < 0.05), and the contents of immune digestion enzymes including lysozyme, alkaline phosphatase and the concentration of complement C4 were markedly enhanced after alpha-ketoglutarate supplementation (P < 0.05). Also, appropriate alpha-ketoglutarate increased the activities of total antioxidant capacity and catalase and prevented the up-regulation in the mRNA expression levels of pro-inflammatory cytokines including tumor necrosis factor-α, interleukin-1β, interleukin-6, and interleukin-8 (P < 0.05). Furthermore, the mRNA expression levels of toll-like receptor 4 (TLR4), and nuclear factor kappa-B (NF-κB) were strikingly increased after infection with Aeromonas hydrophila (P < 0.05), while the TLR4 was strikingly decreased with AKG supplementation (P < 0.05). Moreover, the mRNA expression levels of tight junctions including claudin-1, claudin-3, claudin-7, claudin-11 and myosin light chain kinases (MLCK) were upregulated after alpha-ketoglutarate supplementation (P < 0.05). In summary, the appropriate alpha-ketoglutarate supplementation could increase survival rate, strengthen the intestinal enzyme immunosuppressive activities, antioxidant capacities and alleviate the intestinal inflammation, thereby promoting the intestinal immune responses and barrier functions of Songpu mirror carp via activating TLR4/MyD88/NF-κB and MLCK signaling pathways after infection with Aeromonas hydrophila.